Analysis and Design of a Web-Based Counseling Guidance Management Information System at ABC High School - Diah Ayu; Yahfizham Yahfizham (JUSTINFO | Jurnal Sistem Informasi dan Teknologi Informasi, 2023)
Counseling is a professional support process aimed at helping individuals or groups overcome various personal, emotional, social, or psychological problems. This process involves trained counselors who utilize specialized techniques to provide guidance, support, and advice, facilitating better coping mechanisms and overall well-being. Given the critical role of counseling in fostering mental health and personal development, it is essential to continually improve and enhance counseling services for students. By doing so, counselors can ensure they are providing the most effective and comprehensive support possible. At present, SMA ABC relies on traditional methods such as Microsoft Word and Microsoft Excel to record and store data related to counseling and guidance. While functional, these tools are not optimized for the dynamic and multifaceted nature of counseling work. This traditional approach can be time-consuming and prone to errors, hindering the efficiency and effectiveness of the counseling services provided to students. To address these challenges, a web-based management information system is needed. Such a system would streamline the process of recording, storing, and retrieving information, enabling counselors to complete their tasks more quickly, accurately, and on time. A well-designed web-based system would also facilitate better data analysis and reporting. The development of this system will use the waterfall method, a systematic and sequential approach to software development. This method ensures that all data and information related to the counseling procedures and the system's technical implementation are thoroughly processed and accurately integrated, resulting in a reliable and efficient management tool.